21‐1: Invited Paper: 5291‐ppi Microdisplay Using CAAC‐IGZO FET with Channel Length of 60 nm. Issue 1 (25th September 2020) - Shishido, Hideaki; Katsui, Shuichi; Kobayashi, Hidetomo; Nakagawa, Takashi; Tamatsukuri, Yuki; Uesaka, Shogo; Nagata, Takaaki; Aoyama, Tomoya; Okazaki, Yutaka; Ikeda, Takayuki; Yamazaki, Shunpei
Abstract : For high‐definition microdisplays with more than several thousands of pixels per inch (ppi), c‐axis‐aligned crystal indium‐gallium‐zinc oxide (CAAC‐IGZO) field‐effect transistors (FETs) are effective devices. Based on such a viewpoint, we have fabricated a 5291‐ppi organic light‐emitting diode (OLED) display using CAAC‐IGZO FETs with a channel length of 60 nm.